2012
DOI: 10.1073/pnas.1207347109
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquity and quantitative significance of detoxification catabolism of chlorophyll associated with protistan herbivory

Abstract: Chlorophylls are essential components of the photosynthetic apparati that sustain all of the life forms that ultimately depend on solar energy. However, a drawback of the extraordinary photosensitizing efficiency of certain chlorophyll species is their ability to generate harmful singlet oxygen. Recent studies have clarified the catabolic processes involved in the detoxification of chlorophylls in land plants, but little is understood about these strategies in aquatic ecosystem. Here, we report that a variety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
54
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 53 publications
2
54
0
Order By: Relevance
“…37 We cultured a series of phycophagic protists and a specific unicellular alga as their food, and in an analysis of the pigment extracts of the cultures, we found CPEs to be the sole major chlorophyll derivatives. 35,36 Significantly, we found that CPEs are essentially nonfluorescent in solution (Φ F < 0.002 for cPPB-aE). 35 Under visible-light illumination, cPPB-aE in air-saturated anisole generated no 1 O 2 , whereas parallel experiments with Chl-a and Phe-a rapidly produced 1 O 2 .…”
Section: A Chlorophyll Catabolism By Land Plantsmentioning
confidence: 91%
See 4 more Smart Citations
“…37 We cultured a series of phycophagic protists and a specific unicellular alga as their food, and in an analysis of the pigment extracts of the cultures, we found CPEs to be the sole major chlorophyll derivatives. 35,36 Significantly, we found that CPEs are essentially nonfluorescent in solution (Φ F < 0.002 for cPPB-aE). 35 Under visible-light illumination, cPPB-aE in air-saturated anisole generated no 1 O 2 , whereas parallel experiments with Chl-a and Phe-a rapidly produced 1 O 2 .…”
Section: A Chlorophyll Catabolism By Land Plantsmentioning
confidence: 91%
“…35,36 Significantly, we found that CPEs are essentially nonfluorescent in solution (Φ F < 0.002 for cPPB-aE). 35 Under visible-light illumination, cPPB-aE in air-saturated anisole generated no 1 O 2 , whereas parallel experiments with Chl-a and Phe-a rapidly produced 1 O 2 . 35 The photoexcited S 1 states of the CPEs were immediately quenched to S 0 by internal conversion (È S ic 1), resulting in little chance of intersystem crossing to their T 1 states (Φ T µ 0).…”
Section: A Chlorophyll Catabolism By Land Plantsmentioning
confidence: 91%
See 3 more Smart Citations